Upaya Strategi Pengembangan Kewirausahaan Masyarakat Melalui Home Industri Imur Bahalap Kota Palangka Raya - Wahidin; Joko Setiyono (Jurnal Pendidikan Ilmu Pengetahuan Sosial (JPIPS), 2020)
This study aims to describe: (1) Overview of Community Entrepreneurship Strategies through the Imur Bahalap Home Industry (2) the obstacles faced by managers in Imur Bahalap Entrepreneurship Development (3) Marketing carried out for the Development of the Imur Bahalap This research is a descriptive study with a qualitative approach, with the research subjects namely managers and workers and the community in Imur Bahalap on Street Manjuhan Induk No.20, Palangka Raya City. Data collection methods are interviews, documentation. The data analysis technique that the researchers used was data reduction, data dispay and conclusion drawing. Triangulation is done to explain the validity of the data using sources. The results of the research show that: (1) The entrepreneurial development of Imur Bahalap was first developed by PGRI students who received a grant from the Directorate General of Higher Education through the Student Entrepreneurship program in 2012 and in 2015 PGRI University got another grant for Amplang Production and already has a name. Imur Bahalap which has penetrated into the center of typical souvenirs of the city of Palangka Raya (2 marketing of SME Imur Bahalap marketing online, namely by using the Shoppie shop and tokopedia and offline collaborating with gift shops in Palangka Raya City (3) packaging constraints products with packaging materials using aluminum foil.